Auditory Neuropathy Spectrum Disorder (ANSD) - Nur Azizah Azzahra; Indra Zachreini (Inovasi Kesehatan Global, 2026)
Patients with ANSD may have hearing thresholds that vary from normal to severe hearing loss, but they often have difficulty understanding speech, especially in noisy environments. This condition can be caused by various factors, including genetic mutations (such as in the OTOF gene), preterm birth, perinatal hypoxia, and hyperbilirubinemia. Some adult patients have been reported to develop ANSD following autoimmune disorders such as sensorimotor neuropathy or after chemotherapy with ototoxic agents such as cisplatin. Diagnosis of Auditory Neuropathy Spectrum Disorder (ANSD) begins with a comprehensive medical history to identify risk factors that play a role. A history of preterm birth, severe hyperbilirubinemia requiring exchange transfusion, perinatal hypoxia, ventilator use, and a family history of infection or genetic disorders are major risk factors. In addition, patients or parents often report delayed speech development, inability to understand speech (especially in noisy environments), or a discrepancy between previous hearing test results and the child’s behavioral response. The gold standard for diagnosing ANSD is a combination of: (1) positive OAE and/or CM, (2) absent or abnormal ABR, and (3) absent acoustic reflex. This diagnosis is established only if there is evidence that the cochlea is functioning normally but there is a disruption in auditory nerve transmission. Routine monitoring is conducted to assess hearing and language development and adjust devices and therapy methods according to the patient’s needs. Counseling and education for families are also crucial components to provide optimal support at home and improve the patient’s quality of life. A comprehensive multidisciplinary approach is essential to ensure effective management of ANSD and achieve the best possible outcomes.